ANALISIS SOSIAL EKONOMI DAN PRODUKTIVITAS BURUH PETIK PERKEBUNAN KOPI - Bachrudin; Aris Soelistyo; Muhammad Sri Wahyudi Suliswanto (Program Studi Ekonomi Pembangunan, 2021)
Indonesia is an agrarian country that mostly works in agriculture, so agriculture takes a big deal to the economic growth of both the state and the region. Coffee-picking labor is the occupation of the majority of people in Sukorejo village, to work as coffee-pickers can raise family finances. Therefore, this study aims to analyze the socio-economic and productivity of coffee plantation workers in the Sukorejo village, Tirtoyudo district. This research was carried out using the quantitative descriptive method. The population in this study was 30 coffee-pickers. In this study, it is known that the influencing factors are the independent variables of work experience and working hours. This study uses primary data obtained through questionnaires and is analyzed with multiple cross-sectional regression using Statistical Package for the Social Sciences (SPSS) 23. It is observed that work experience and working hours have a positive and significant effect on productivity. The coefficient of determination (R-squared) value is 0.417 in which showed the variables of work experience and working hours. This result suggests that the productivity variable is 41.7%, and the remaining 58.3% explained by variables outside the model.